Evaluación de Riesgos laborales en las áreas de la Dirección de Gestión Ambiental, Salubridad e Higiene del GADM-Riobamba en 2024 - Cóndor Jami, Esteban Andrés (2025)
The present research study evaluated occupational risks in the areas of the Environmental Management, Health, and Hygiene Department of the GADM-Riobamba, with the objective of establishing prevention measures based on methodologies supported by Ecuadorian and international regulations. A descriptive and non-experimental approach was used, as variables were not manipulated, supported by field observations that allowed for a detailed analysis of current conditions in the department. This methodology facilitated an accurate diagnosis of existing risks, and the subsequent implementation of corrective actions based on real data. To identify hazards, surveys and interviews were conducted, the results of which revealed that workers were exposed to physical, ergonomic, biological, and psychosocial risks, derived from a deficient occupational safety culture. In the assessment phase, recognized normative instruments were used, while in the measurement phase, the level of risk exposure was quantified, prioritizing the hierarchy of controls (elimination, substitution, administrative controls, and PPE). The study identified significant risks that compromise the integrity and health of the personnel and recommended the implementation of corrective and preventive measures to ensure safe working conditions and compliance with current legislation. These findings highlight the need to strengthen the prevention culture in the organization, aligning with international occupational health and safety standards.